Lyophyllum decastes fruiting body polysaccharide alleviates acute liver injury by activating the Nrf2 signaling pathway. Issue 4 (2nd February 2022) - Zhang, Fengpei; Xu, Hui; Yuan, Yuan; Huang, Haichen; Wu, Xiaoping; Zhang, Junli; Fu, Junsheng
Abstract : LDFP have high antioxidant, hypoglycemic, hypolipidemic, hepatoprotective, anti-tumor, and anticancer activities. Abstract : Polysaccharides have high antioxidant, hypoglycemic, hypolipidemic, hepatoprotective, anti-tumor, and anticancer activities. In this study, the ability of the Lyophyllum decastes fruiting body polysaccharide (LDFP) to protect against CCl4 -induced acute liver injury in mice by activating the Nrf2 pathway was studied. LDFP can inhibit the activity of ALT, AST, TC, TG, tumor necrosis factor (TNF-α), and interleukin-6 (IL-6) in serum; significantly improve the inflammatory state of the liver; increase the activity of superoxide dismutase (SOD) and the glutathione (GSH) content; decrease the malondialdehyde (MDA) content; alleviate the toxicity caused by reactive oxygen species; and alleviate liver injury. Immunohistochemistry and western blot showed that LDFP can activate the Nrf2 pathway, up-regulate the expression of Nrf2, down-regulate the expression of Keap1, and increase the expression of the anti-oxidation factors HO-1 and CuZn-SOD. At the same time, it was found that the expression of the transcription factors TLR-4 and NF-κB were decreased in the NF-κB signaling pathway, the synthesis and secretion of the pro-inflammatory factors IL-6 and TNF-α were decreased consequently. These results suggest that LDFP protects the liver by activating the Nrf2 pathway and reducing the inflammatory response. Generally, the results of this study could be used to aid the development of hepatoprotective products and their application.